Saúde, crescimento e rendimento de filé de tilápia do nilo (Oreochromis niloticus), alimentada com rações contendo fosfatidilcolina - Braga, Milene Neves Ferreira (2022)
The intensification of aquaculture production systems requires adequate nutrition to optimize the productive performance and fish health, so phosphatidylcholine of plant origin has been used in fish feeding, demonstrating positive effects. In this context, the objective of this study was to evaluate the health, growth, and yield of tilapia fillets in the growing and fattening phases, fed with increasing doses of phosphatidyl-choline of vegetable origin (0, 200, 400, 600 mg and 800mg/kg of feed) and 84.87 mg/kg of choline chloride. Specifically, the thesis is subdivided into two chapters, the first chapter starting with the literature review in which themes related to the thesis are addressed. In the second chapter, the inclusion of increasing doses of phosphatidylcholine of plant origin (0, 200, 400, 600 mg, and 800 mg/kg of feed) and choline chloride in diets for Nile tilapia (Oreochromis niloticus), in a net tank system (4 m3) with constant aeration. A total of 8,400 juvenile Nile tilapia (Oreochromis niloticus), sexually reverted ( 18 g) were used during a period of 117 days, which includes the growth and fattening phases. The animals were distributed in a completely randomized design, consisting of 6 treatments and 4 replications, the net tanks were considered as experimental units and each experimental unit had 350 fish. After this period, zootechnical performance indices, plasma biochemical parameters, oxidative stress indicators, proximate composition of muscle, liver, and viscera and hepatic tissue were evaluated. The diet with phosphatidylcholine interfered in the zootechnical performance parameters – final weight, daily weight gain, biomass gain and apparent feed conversion (P<0.05), for the final weight, daily weight gain and weight gain and biomass indices, the best performance was at the dose of 600 mg/kg, when compared to the inclusion of 400mg/kg of phosphatidylcholine of vegetable origin, and the apparent feed conversion was better (P<0.05) in the treatment with 800 mg/kg, when compared with the inclusion of 600 mg/kg. As for the biochemical parameters of plasma, the diet interfered in the levels of triglycerides, which were significantly (P<0.05) lower in the diet containing 600 mg/kg, when compared at levels of 400mg/kg and 800mg/kg of phosphatidylcholine of vegetable origin. The antioxidant status was not influenced by the diet (P>0.05) offered. The proximate composition of different tissues underwent changes (P<0.05), especially in the contents of ethereal extract of the liver and viscera and in the contents of crude protein in muscle and liver, and the tilapia fed with 800 mg/kg showed higher deposition of hepatic ether extract, and the level of 600mg/kg showed a reduction of ether extract in the viscera. For the evaluation of hepatic tissue, the inclusion of phosphatidylcholine of vegetable origin in the diet showed no changes (P>0.05). Considering the nutritional factors involved in this thesis, it can be concluded that the use of 600 mg/kg of phosphatidylcholine in the diet of Nile tilapia (Oreochromis niloticus) directly contributes to an improvement in zootechnical performance indices and biochemical parameters of plasma, more specifically linked to a reduction in plasma triglyceride levels. The doses of phosphatidylcholine added to the diet did not cause negative effects on the antioxidant status, nor on the liver of the tilapia, but further research related to these parameters needs to be carried out.